Processos educativos entre jovens na construção de uma cartilha educativa sobre direitos sexuais e reprodutivos - Barbosa, Daniela de Castro (Universidade Federal de São Carlos, 2008)
Facing the problem of addressing the Sexual and Reproductive Rights in the school institution and recognizing the capacity that the young has in acting as a protagonist of their learning process of education, this research aimed as general objective to observe, to understand and to analyze educational processes unchained among eight young in the age group from thirteen to fourteen years to become involved in the elaboration of educational material on Sexual and Reproductive Rights. It was a descriptive study of qualitative character based on the Paulo Freire perspective of the education understanding as a dialogical process. The data collection was made in the months of April to October of 2007, in a state school in the city of Ribeirão Preto, having been used as instruments for collection the conversation wheels and the annotations in field diaries. At first educational actions were accomplished with all the students of the seventh and eighth series, which allowed us to present the theme of the Sexual and Reproductive Rights and to invite them to participate voluntarily in the research. Later, the research participants chose for voting which rights they would like to discuss in our dialogues. From here, there were proposed activities with problems that unchained the conversation wheels on the sexual and reproductive rights, allowing contextualizing knowledge, practices, opinions and expectations of the young. Finally, the research participants reflected about the sexual and reproductive rights to develop an educational book, with texts, drawings and researches of their own authorship. The discoveries were organized for themes of analysis. The results showed that the young possess knowledge, of their body, their health, their sexuality and these was demonstrated with questions and curiosities to share knowledge. They actively participated in their process of teaching and learning and have brought forth discussions on the issues that afflict then in their daily lives, such as the gender relationships, the dialogue lack in the affectionate relationships, the abortion, among others. We concluded that when the young interacts with their group of equals in the construction of educational material on sexual and reproductive rights they express themselves with easiness, understands the sexuality as being part of the human, recognizes the importance of the prevention and tries to take attitudes that lead to the exercise of their rights.
Keywords: Processo educativo; Direitos sexuais e reprodutivos; Juventude; Educational processes; Reproductive Rights; Youth; CIENCIAS HUMANAS::EDUCACAO